Räuber – Priester – Königskinder - Bickel, Susanne (LIBRUM Publishers & Editors LLC, 2021)
This is the first volume of the complete publication of the research carried out in the two undecorated shaft tombs KV 40 and KV 64 in the Valley of the Kings, near Luxor, Egypt. This volume presents all the inscribed material from the Eighteenth Dynasty (ca. 1400–1350) together with the pottery and the jar stoppers. Inscribed wooden tags, hieratic inscriptions preserved on pottery jars, canopic vessels, and different types of sealings yield precious information on the large group of people buried in KV 40. The material attests the names, titles and sometimes institutional affiliations of over 30 individuals, a majority of women, all belonging to the family and entourage of pharaoh Amenhotep III. Only one unidentified woman was buried in the much smaller tomb KV 64. These findings represent the first substantial information on the use of undecorated tombs in the royal necropolis. They give insight into little know categories of objects and almost unknown techniques of jar inscription. They also reveal very specific practices performed for the funerals and burials of members of the royal family and entourage.